2006
DOI: 10.1248/cpb.54.196
|View full text |Cite
|
Sign up to set email alerts
|

Expeditious Syntheses of Conjugated Allenyl Esters and Oxazoles through a Cascade Reaction of .ALPHA.-Alkynyl Malonates under Alkaline Conditions

Abstract: Since the development of various synthetic methods for the achiral and chiral allenes, extensive studies on the structure and reactivity of the characteristic allenes have been performed. [1][2][3][4][5][6][7][8][9] Allenylic compounds have been efficiently utilized as a key intermediate to synthesize biologically active natural products. [10][11][12] The specific reactivities of allenylic compounds have been widely applied to carbon-carbon and carbon-hetero atom cyclizations, aldol reactions, DielsAlder react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 45 publications
(75 reference statements)
0
3
0
Order By: Relevance
“…When reagents possess nucleophilic and electrophilic sites, the formed hemiacetal attacks the electrophilic site of the nucleophile via dipolar cycloaddition (path d ). 7 Conversely, dehydration of the hemiacetal forms an electron-deficient double bond (path e ), 8–10 which subsequently accepts the addition of less nucleophilic reagents, such as pyrrole. 10…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When reagents possess nucleophilic and electrophilic sites, the formed hemiacetal attacks the electrophilic site of the nucleophile via dipolar cycloaddition (path d ). 7 Conversely, dehydration of the hemiacetal forms an electron-deficient double bond (path e ), 8–10 which subsequently accepts the addition of less nucleophilic reagents, such as pyrrole. 10…”
Section: Introductionmentioning
confidence: 99%
“…12 Although N -acetylimine is directly prepared from DEMO via the aza-Wittig reaction, the N -substituent is limited to an acetyl group. 9 In our previous work, we demonstrated that DEMO efficiently reacted with versatile acid amides to afford the corresponding hemiacetals, 4 which serves as precursors of N -acylimines modifiable by the acyl group upon dehydration.…”
Section: Introductionmentioning
confidence: 99%
“…Because the presence of a terminal alkyne is crucial for the success of the approach, these methodologies are limited to the synthesis of 5-methyl-substituted oxazoles. Inspired by Nagao and co-workers, who reported the formation of trisubstituted oxazoles under basic reaction conditions, [18] Ciufolini described the condensation of an aluminum acetylide with an α-chloroglycinate for the preparation of various polysubstituted oxazole-4-carboxylic ester building blocks. [11b,19] Unfortunately, the aluminum-catalyzed strategy suffers from moderate yields, limited substrate scope, and exhibits poor functional-group tolerance.…”
Section: Introductionmentioning
confidence: 99%